A Cross-Sectional Study of Marital Women’s Violence in Rural Nepal - Acharya, Milan (Tribhuvan University Journal, 2024)
The purpose of this paper is to explore the situation of domestic violence among married women in Arghakhanchi, Nepal. A quantitative cross-sectional study design was used. It is found that females from Brahmin families had a higher percentage of corporal punishment than females of other ethnic groups (30.9% vs. 26.4%, p=0.001). Married women of age 25 and less were victimized by corporal punishment (58.3 %, p=0.001). Corporal punishment was 1.66 times higher in married women of the reproductive age group victimized by message mistreatment. It is linked to women’s bullying through messages [AOR: 1.43; 95 %]. It means with a 95% confidence interval, that women who encounter bullying via SMS are 1.43 times more likely to become victims of domestic violence than women who do not. This implies that the two variables have a moderately positive connection. It is recommended that Brahmin younger married women (age 25 and under) should be the focus of interventions, as they seem to be more susceptible to physical punishment. Additionally, as message mistreatment and women’s bullying through messages are strongly associated with a higher likelihood of domestic violence, addressing these issues should be a top concern.